2022
DOI: 10.1002/ece3.9397
|View full text |Cite
|
Sign up to set email alerts
|

The effects of local filtering processes on the structure and functioning of native plant communities in experimental urban habitats

Abstract: Despite a growing literature‐base devoted to document biodiversity patterns in cities, little is known about the processes that influence these patterns, and whether they are consistent over time. In particular, numerous studies have identified the capacity of cities to host a rich diversity of plant species. This trend, however, is driven primarily by introduced species, which comprise a large proportion of the urban species pool relative to natives. Using an experimental common garden study, we assessed the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 110 publications
1
3
0
Order By: Relevance
“…A higher proportion of spatial structure in the explained variance of species composition and SES_FDis for native plant species (Figure 3) suggested that community assembly of native species would be largely determined by dispersal limitation (Beninde et al, 2015;Borowy & Swan, 2022;Reeve et al, 2022), which supported our hypothesis (Figure 1). Because we investigated a limited number of local environmental variables, however, explained variance of species composition and functional diversity for native species could be enhanced by including environmental factors such as microclimate that can directly regulate plant establishment, growth, and environment.…”
Section: Community Assembly Of Plant Species Across Urban Vacant Lotssupporting
confidence: 74%
See 3 more Smart Citations
“…A higher proportion of spatial structure in the explained variance of species composition and SES_FDis for native plant species (Figure 3) suggested that community assembly of native species would be largely determined by dispersal limitation (Beninde et al, 2015;Borowy & Swan, 2022;Reeve et al, 2022), which supported our hypothesis (Figure 1). Because we investigated a limited number of local environmental variables, however, explained variance of species composition and functional diversity for native species could be enhanced by including environmental factors such as microclimate that can directly regulate plant establishment, growth, and environment.…”
Section: Community Assembly Of Plant Species Across Urban Vacant Lotssupporting
confidence: 74%
“…Because we investigated a limited number of local environmental variables, however, explained variance of species composition and functional diversity for native species could be enhanced by including environmental factors such as microclimate that can directly regulate plant establishment, growth, and environment. Nonetheless, previous studies have suggested that native species may respond to local filtering pressures by changing their functional traits over time (Borowy & Swan, 2022), making environmental filtering less important for native species assembly than dispersal limitations. Although urban ecosystems are primarily affected by human activities such as habitat conversion and fragmentation of remaining habitats (Williams et al., 2009), our results highlight the primary importance of dispersal limitation in driving native plant species assembly in urban systems (Aronson et al., 2016; Borowy & Swan, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations